ANALISIS PENGARUH OPERATING EXPENSES TO OPERATING INCOME (RASIO BOPO) DAN COST EFFICIENCY RATIO TERHADAP NET PROFIT MARGIN PADA BANK MANDIRI CABANG X SURABAYA - Arif, Bagus Muhamad (Jurnal Akuntansi AKUNESA, 2014)
Earnings growth can be analyzed with fundamental analysis, by looking at a company's financial ratios. This study was conducted to examine the effect of operational efficiency ratio (OER) or BOPO ratios and cost efficiency ratio (CER) of the net profit margin (NPM). Object of this research is the X branch of Mandiri Bank in Surabaya. and the backdrop of the bank as the authors make the research object because the level of the bank's acquisition of NPM significant rmenurun in 2011. This study uses a descriptive analysis of the data by examining documentation X branch of Mandiri Bank in Surabaya. The data required in the form of quantitative data, namely the annual financial statements for 2010-2012. Here indicate that the Operating Costs: Operating Income a negative effect on earnings growth. Overhead ratio as well as the effect on net profit margin also acquired Bank. it can be concluded that the ratio of Operating Expenses: Operating Income (ROA ratio) and Overhead Cost Ratio (CER ratio) affect earnings growth.Keywords : Operational Efficiency Ratio (BOPO), CER, NPM